Degree based Topological indices of Subdivision Graph - Wang, Caiyun; Zhang, Shumin; Li, He (Discontinuity, Nonlinearity, and Complexity, 2026)
Several degree based topologcal indices are usually used to characterize chemical compounds. Such as Randić index, the sum-connectivity index, the harmonic index, $ABC$ index, and the geometric-arithmetic index etc. In the paper, we compute the values about the topological indices of subdivision graph.